Evaluasi Kritis Pemerintah Provinsi Sumatera Utara dalam Penanggulangan Ketimpangan Sosial - Harahap, Juliadi Zurdani; Kholil, Syukur (Jurnal Studi Ilmu Sosial dan Politik, 2024)
Purpose: This study aims to critically evaluate the North Sumatra Provincial Government's strategies in addressing social inequality using the Stimulus-Organism-Response (SOR) model, focusing on how policies are formulated and implemented to tackle disparities in income, education, healthcare, and infrastructure access. Methodology/approach: The research employs a qualitative approach, using case studies and in-depth interviews with key informants from government institutions, such as Bappeda, the Department of Social Affairs, and the Department of Education. Secondary data, including official reports and statistics from the Central Bureau of Statistics (BPS), is also analyzed. The data is processed through qualitative content analysis to identify key themes related to the government's response to social inequality. Results/findings: The study finds that while the North Sumatra government has launched several policies to address social inequality, including social assistance programs, infrastructure development, and education access improvements, these initiatives face significant challenges. These include uneven resource allocation, political interference, and logistical issues in reaching remote areas. The findings also highlight a lack of effective coordination between government agencies, which hampers the implementation of policies, particularly in rural and isolated regions. Limitations: The study's scope is limited to North Sumatra Province, and the findings may not be fully generalizable to other regions with different socio-economic contexts. Additionally, the reliance on qualitative data, such as interviews and document analysis, introduces the risk of subjective bias from informants and limited access to comprehensive quantitative data. Contribution: This research contributes to the literature on public policy and social inequality by applying the SOR model to a provincial context in Indonesia. It provides valuable insights into the challenges faced by local governments in addressing inequality and offers recommendations for improving policy formulation and implementation processes. The findings can inform future policy-making efforts and contribute to more effective responses to social inequality in other regions.